NPLs — The Solution Recipe for Albania - Shehu, Elona; Meka, Elvin (European Journal of Economics and Business Studies, 2015)
The quality of the loan portfolio in Albanian banking system is facing many obstacles during the last decade. In this paper we look at possible determinants of assets quality. During the recent financial crisis commercial banks were confronted with deteriorating asset quality that threatened not only the banking industry, but also the stability of the entire financial system. This study aims to examine the correlation between non-performing loans and the macroeconomic determinants in Albania during the last decade. NPLs are considered to be of a high importance as they represent the high risk exposure of banking system. A solid bank with healthy assets increases the market efficiency. Our approach is based on a panel data regression analysis technique from 2005-2015. Within this methodology this study finds robust evidence on the existing relationship between lending interest rate, real GDP growth and NPLs. We expect to find a negative relationship between lending interest rate and asset quality. Further we assume an inverse relationship between GDP growth and non-performing loans, suggesting that NPLs decrease if the economy is growing. Furthermore this study proposes a solution platform, which looks deeper into the possibility of creating a secondary active market for troubled loans, restructuring the banking system or implementing the Podgorica model. This research paper opens a new lieu of discussion in terms of academic debates and decision-making policies.
Keywords: Non Performing Loans, Albania, lending interest rate, real GDP growth, bank restructuring, secondary market